2013
DOI: 10.1136/bmj.f6150
|View full text |Cite
|
Sign up to set email alerts
|

Should athletes be allowed to use performance enhancing drugs?

Abstract: Stories about illegal doping in sport are a regular occurrence. Julian Savulescu argues that rather than banning performance enhancing drugs we should regulate their use, but Leon Creaney and Anna Vondy say this would lead to escalating use and call for tougher enforcement

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Doping is viewed as a moral issue by both athletes (e.g., Erickson, McKenna, & Backhouse, 2015) and academics (e.g., Atry, Hansson, & Kihlbom, 2013;Corlett, 2013;Corlett, Brown, & Kirkland, 2013). However, some academics have argued that doping does not violate the spirit of sport (e.g., Savulescu, Creaney, & Vondy, 2013), and reported that sportspersonship does not predict doping (e.g., Barkoukis, Lazuras, Tsorbatzoudis, & Rodafinos, 2011; cf.…”
Section: The Effects Of Moral Disengagement Mechanisms On Doping Likementioning
confidence: 99%
“…Doping is viewed as a moral issue by both athletes (e.g., Erickson, McKenna, & Backhouse, 2015) and academics (e.g., Atry, Hansson, & Kihlbom, 2013;Corlett, 2013;Corlett, Brown, & Kirkland, 2013). However, some academics have argued that doping does not violate the spirit of sport (e.g., Savulescu, Creaney, & Vondy, 2013), and reported that sportspersonship does not predict doping (e.g., Barkoukis, Lazuras, Tsorbatzoudis, & Rodafinos, 2011; cf.…”
Section: The Effects Of Moral Disengagement Mechanisms On Doping Likementioning
confidence: 99%
“…Therefore, experts point out quite reasonably that the distinction between prohibited and permitted substances is determined exclusively by the administrative decision of WADA, relying on the non-scientific definition of doping, subjective criteria and vague ideas about the "spirit of sports" rather than on scientific and medical foundations [13,49]. Even greater confusion is caused by WADA's constant manipulations with the content of the Prohibited List, allowing the use of certain substances and prohibiting the use of others, transferring permitted substances to the Prohibited List and vice versa transferring prohibited substances to the Permitted List [40], as well as introducing absolutely unreasonable norms of banned substances in samples of athletes.…”
Section: Criteria For Including Substances and Methods In The Prohibimentioning
confidence: 99%
“…Actual crisis that may not only to discredit the Olympics, but also may lead to the collapse of the Olympic movement, began with the establishment of WADA and isolation from the anti-doping fight of authorities in the field of sports and health science and assigning responsibilities to deal with the problem on "effective managers" [47]. The inadmissibility of this situation finds a convincing confirmation in the writings of many authoritative experts seriously concerned about the critical situation in Olympic sports with regard to the WADA's methodology and practice in the anti-doping fight [4,27,28,31,40,49].…”
Section: Prospects Of Finding a Solution To The Doping Problem In Sportmentioning
confidence: 99%
“…Only two of them are still doping unspotted." (Savulescu et al, 2013). The above necessitates application of allowed pharmacological preparations of ergogenic character, however, in many cases the process of elite athletes' preparation is not without the use of WADA banned anabolic means.…”
Section: Problem Statementmentioning
confidence: 99%